Composite material for coating-free one-time formed photovoltaic frame and application of composite material

By using composite materials with specific ratios, including epoxy resin, bisanhydride precuring bodies and anti-UV nanoadditives, the existing photovoltaic frame materials are solved, and photovoltaic frame materials with high intensity, low thermal expansion coefficient and excellent UV resistance are achieved.

CN119798926AActive Publication Date: 2025-04-11JIANGXI LONGZHENG TECH DEV CO LTD
View PDF 8 Cites 0 Cited by

Patent Information

Application Number
CN202411945712.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-27
Publication Date
2025-04-11
Estimated Expiration
2044-12-27

AI Technical Summary

Technical Problem

Existing photovoltaic frame materials such as aluminum alloys are costly and have complex production processes. In addition, resin materials have compatibility problems in improving UV resistance, strength and thermal stability, and it is difficult to meet multiple performance requirements of photovoltaic frames at the same time.

Method used

Using a composite material, including bisphenol A type epoxy resin E-55, bisanhydride precuring body, anti-ultraviolet nano additives, triphenyl phosphate and defoaming agent, photovoltaic frame materials with high strength, low thermal expansion coefficient and excellent UV resistance are prepared by specific preparation methods.

Benefits of technology

The photovoltaic frame material has low density, high strength, strong weather resistance and excellent thermal stability, which reduces production costs and improves the overall performance of the material.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119798926A_ABST
    Figure CN119798926A_ABST
Patent Text Reader

Abstract

The invention relates to the technical field of epoxy resin, in particular to a composite material for a coating-free one-time formed photovoltaic frame and application of the composite material. The composite material is prepared from 8-10 parts of bisphenol A epoxy resin E-55, 10-12 parts of a dianhydride precuring body, 0.8-1 part of an anti-ultraviolet nano additive, 1-1.5 parts of triphenyl phosphate and 0.02-0.03 part of a BYK-022 defoaming agent, the dianhydride precuring body is terpene maleic anhydride prepared by carrying out heating catalytic reaction on alpha-terpinene, maleic anhydride and a catalyst benzenesulfonic acid in a dichloromethane solvent; uniformly mixing the mixture with tetrafluorophthalic anhydride which is ground into powder in an ultrasonic manner, and then adding bisphenol A epoxy resin E-55 and uniformly stirring to obtain the paint. The prepared composite material has high strength and low thermal expansion coefficient, and also has excellent ultraviolet resistance, and the photovoltaic frame prepared from the composite material has the characteristics of low density, high strength, strong weather resistance and excellent thermal stability.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of epoxy resins, and in particular to a composite material for painting-free one-time forming of a photovoltaic frame and an application thereof. Background Art

[0002] With the rapid development of the photovoltaic industry, the application demand for photovoltaic modules continues to increase, resulting in a sharp increase in the demand for photovoltaic panel frame materials. The frame material of photovoltaic modules is mainly made of aluminum alloy. Because of its low density, high strength, good plasticity and excellent electrical conductivity, thermal conductivity and corrosion resistance, aluminum alloy can form a dense oxide layer after surface treatment, providing effective anti-corrosion protection, and thus becomes the first choice for photovoltaic frame materials.

[0003] However, with the continuous advancement of photovoltaic technology, photovoltaic modules have higher and higher requirements for frame materials. Although aluminum alloy has many advantages, its cost in the production process is relatively high and the production process is relatively complicated. In particular, it requires multiple precision processing and surface treatments during the manufacturing process, which makes the overall production cost high. In addition, the heavy weight of aluminum alloy frames is also a constraint. In some occasions with strict requirements on installation weight, such as rooftop photovoltaic systems, lighter frame materials are needed to reduce the overall load.

[0004] Resin materials have a lower density and are lighter than traditional aluminum alloys. Common thermosetting resins (such as epoxy resins, polyester resins, etc.) are also relatively low in cost and can be used as preferred materials for making photovoltaic frames. In order to ensure that the photovoltaic frames can remain stable when placed under light, anti-ultraviolet agents, flame retardants, reinforcing fillers and other substances are often added to the resin materials. Due to compatibility issues between these substances and the resin materials, too much anti-ultraviolet agents, flame retardants and reinforcing fillers cannot be added to the resin to avoid performance degradation. Therefore, these substances have limited effect on improving the performance of the resin materials, making it difficult for the resin materials to simultaneously obtain excellent anti-ultraviolet performance, high strength and thermal stability. Summary of the invention

[0005] In order to solve the above-mentioned technical defects, the present invention has developed a composite material for painting-free one-time forming photovoltaic frames which has high strength and low thermal expansion coefficient as well as excellent UV resistance. The photovoltaic frames prepared from this material have the characteristics of low density, high strength, strong weather resistance and excellent thermal stability.

[0006] To achieve the above-mentioned object, in a first aspect, the present invention provides a composite material for a one-time molding photovoltaic frame without painting, which comprises the following components: 8-10 parts of bisphenol A epoxy resin E-55, 10-12 parts of bisanhydride precured body, 0.8-1 parts of anti-ultraviolet nano additives, 1-1.5 parts of triphenyl phosphate and 0.02-0.03 parts of BYK-022 defoaming agent;

[0007] The dianhydride precured body is prepared by heating alpha-terpinene, maleic anhydride and catalyst benzenesulfonic acid in a dichloromethane solvent to obtain terpene maleic anhydride, ultrasonically mixing with ground tetrafluorophthalic anhydride, and then adding bisphenol A epoxy resin E-55 and stirring evenly.

[0008] The anti-ultraviolet nano additive is firstly prepared by reacting 2-sulfonate terephthalic acid, Al(NO3)3·9H2O and flake graphite powder with N,N-dimethylformamide to prepare 2-sulfonate terephthalic acid solution, Al(NO3)3 solution and graphene dispersion respectively, then mixing them for high-temperature heating reaction, centrifugally filtering to obtain nano-organic metal particles loaded with graphene, and then dissolving fulvic acid in sodium hydroxide solution, adding a surfactant to obtain a fulvic acid solution, and then mixing the nano-organic metal particles loaded with graphene, glutaraldehyde and the fulvic acid solution to stir the reaction, and then washing and drying to obtain the anti-ultraviolet nano additive.

[0009] In a second aspect, the present invention provides a method for preparing a composite material for a one-time molding photovoltaic frame without painting, comprising the following steps:

[0010] S1: Preparation of graphene-loaded nano-organic metal particles;

[0011] S2: Preparation of UV-resistant nano-additives;

[0012] S3: Preparation of dianhydride precured body and compounding of epoxy resin.

[0013] Furthermore, step S1 of preparing graphene-loaded nano-organic metal particles comprises the following steps:

[0014] S1.1: 4-6 parts of 2-sulfonated terephthalic acid and 0.6-0.8 parts of anhydrous sodium acetate are placed in a container, and then 20-25 parts of N, N-dimethylformamide are added, and magnetic stirring is performed at a speed of 250-300 rpm for 30-35 minutes to obtain a 2-sulfonated terephthalic acid solution, and then 2-3 parts of Al(NO3)3·9H2O and 25-30 parts of N, N-dimethylformamide are mixed and magnetic stirring is performed until Al(NO3)3·9H2O is completely dissolved to obtain an Al(NO3)3 solution;

[0015] S1.2: 0.3-0.5 parts of flake graphite powder are placed in a container, 4-5 parts of ethanol solution with a concentration of 35-40% are added, and then stirred at a stirring speed of 400-500rpm for 10-15 minutes, and filtered and dried after standing for 15-20 minutes to obtain clean flake graphite, and the clean flake graphite and 0.2-0.3 parts of polyvinyl pyrrolidone are mixed and placed in a container, 8-10 parts of N, N-dimethylformamide are added and stirred evenly, and then placed in an ultrasonic disperser, and ultrasonic treatment is performed for 3-5 hours at an ultrasonic power of 50-60w to obtain a graphene dispersion;

[0016] S1.3: The 2-sulfonate terephthalic acid solution and Al(NO3)3 solution obtained in step S1.1 are mixed and placed in a container, and ultrasonically treated at an ultrasonic frequency of 25-30 kHz for 15-20 minutes, and then transferred to a reactor and heated at 120-140°C for 10-12 hours, and then transferred to an ultrasonic disperser, and the graphene dispersion obtained in step S1.2 is added, and ultrasonically treated at an ultrasonic frequency of 25-30 kHz for 8-10 minutes, and then transferred to a reactor and heated at 120-140°C for 60-65 hours to obtain a mixed reaction liquid. After the reactor is naturally cooled to room temperature, the mixed reaction liquid is placed in a centrifuge and centrifuged at a speed of 8000-10000 rpm for 5-8 minutes, and then filtered, and washed with N,N-dimethylformamide and methanol for 2-3 times respectively to obtain nano-organic metal particles loaded with graphene.

[0017] Furthermore, the preparation of the anti-ultraviolet nano additive in step S2 comprises the following steps:

[0018] S2.1: dissolving fulvic acid in a sodium hydroxide solution having a concentration of 0.1-0.2 g / L to prepare a fulvic acid alkali solution having a concentration of 0.06-0.08 g / L, then adding 0.1-0.2 wt % of a surfactant, stirring evenly, adding HCl solution to adjust the pH to 7.2-7.5, and filtering using a 0.5-0.6 μm filter membrane to obtain a fulvic acid solution;

[0019] S2.2: Place the graphene-loaded nano-organic metal particles obtained in step S1.3 in 120-150 parts of fulvic acid solution, add 0.02-0.03wt% glutaraldehyde, and then continue stirring at a speed of 200-250rpm for 8-12 hours, and then centrifuge at a speed of 6000-7000rpm for 4-5 minutes to obtain fulvic acid-doped nanoparticles, wash them with methanol and deionized water 2-3 times respectively, and then place them in a vacuum drying oven at a temperature of 60-65°C for 20-24 hours to obtain an anti-ultraviolet nano-additive.

[0020] Furthermore, step S3 of preparing the dianhydride precured body and compounding the epoxy resin comprises the following steps:

[0021] S3.1: α-terpinene and maleic anhydride are placed in a container at a molar ratio of 1:(1-1.05), 0.1-0.5wt% of benzenesulfonic acid is added, and then 40-60 times the mass of dichloromethane is added, and the mixture is stirred evenly and heated to 60-80°C. The mixture is kept warm for reaction for 10-12 hours, and the reaction solution is stirred for 10-15 minutes every 40-60 minutes during the reaction. After stopping the heating, the mixture is naturally cooled to room temperature, and then filtered to remove solid impurities. The mixture is then placed in a rotary evaporator and rotary evaporated at 40-50°C at a speed of 80-100rpm until the mass does not change, thereby obtaining terpene maleic anhydride;

[0022] S3.2: Grind 1-2 parts of tetrafluorophthalic anhydride into powder, pass through a 180-200 mesh sieve, and mix them together with 4-6 parts of terpene maleic anhydride in an ultrasonic water bath to obtain a dianhydride suspension, maintain the temperature at 40-50°C, drain 1-2 parts of bisphenol A epoxy resin E-55 into the dianhydride suspension along a glass rod, and stir for 10-15 minutes to obtain a dianhydride precured body;

[0023] S3.3: Place 8-10 parts of bisphenol A epoxy resin E-55, 10-12 parts of dianhydride precured body, 0.8-1 part of anti-UV nano additive, 1-1.5 parts of triphenyl phosphate and 0.02-0.03 parts of BYK-022 defoaming agent in a container, stir at 40-50°C and speed of 500-600rpm for 20-30 minutes to obtain a composite material for painting-free one-time molding of photovoltaic frames.

[0024] Furthermore, the surfactant in step S2.1 is hexadecyltrimethylammonium bromide.

[0025] Furthermore, in step S3.2, the mixture is mixed evenly in an ultrasonic water bath, wherein the temperature of the ultrasonic water bath is 60-65° C. and the ultrasonic frequency is 28-30 kHz.

[0026] In the third aspect, the present invention also provides the application of the composite material for the one-time molding of the photovoltaic frame without painting in the photovoltaic frame. The composite material for the one-time molding of the photovoltaic frame without painting can be extruded in a double-screw extruder, and then pultruded once in a mold to obtain a photovoltaic frame. The obtained photovoltaic frame has good UV resistance, thermal stability and strength.

[0027] The beneficial effects are as follows: 1. The present invention prepares terpene maleic anhydride by catalyzing alpha-terpinene and maleic anhydride with benzenesulfonic acid, then grinds tetrafluorophthalic anhydride into powder and uniformly mixes it with liquid terpene maleic anhydride by ultrasonic to prepare a dianhydride suspension, and then introduces a small amount of bisphenol A epoxy resin E-55 to perform pre-curing and cross-linking with the dianhydride suspension. In the subsequent mixing process of the obtained dianhydride precured body with the epoxy resin, tetrafluorophthalic anhydride substituted with four fluorine atoms can provide high thermal stability and low thermal expansion coefficient for the epoxy resin, while terpene maleic anhydride can provide a good curing environment for tetrafluorophthalic anhydride which is solid at room temperature and has poor compatibility with the epoxy resin, thereby avoiding the problems of slow reaction and incomplete reaction with the epoxy resin, thereby improving the degree of network cross-linking. The synergistic effect of tetrafluorophthalic anhydride and terpene maleic anhydride can effectively improve the thermal stability of the epoxy resin, reduce its thermal expansion coefficient, and enhance its strength.

[0028] 2. The present invention prepares 2-sulfonate terephthalic acid solution, Al(NO3)3 solution and graphene dispersion by respectively reacting 2-sulfonate terephthalic acid, Al(NO3)3·9H2O and flake graphite powder with N,N-dimethylformamide, and then mixes them for high-temperature heating reaction, and centrifuges to obtain nano-organic metal particles loaded with graphene. In the process of forming an Al-based metal organic framework, graphene can help the Al-based metal organic framework to form more uniform nano-particles, reduce agglomeration, and obtain nano-particles with smaller particle size. The pore structure of the metal organic framework can fully load the graphene, thereby enhancing the strength of the subsequent epoxy resin. In addition, the Al-based metal organic framework can provide Al to fully shield ultraviolet rays with wavelengths in the range of 100 nanometers to 400 nanometers. Doping in the epoxy resin material not only improves the anti-ultraviolet performance, but also the organic framework has good compatibility with the epoxy resin, thereby avoiding the doping of nano-materials to affect the strength of the composite material.

[0029] 3. The present invention dissolves fulvic acid in a sodium hydroxide solution, adds a surfactant to obtain a fulvic acid solution, and then mixes graphene-loaded nano-organic metal particles, glutaraldehyde and the fulvic acid solution for stirring reaction to obtain an anti-ultraviolet nano-additive, so that fulvic acid is doped in the graphene-loaded nano-organic metal particles, wherein the fulvic acid contains a large number of phenolic hydroxyl groups, carboxyl groups and other functional groups, which can react chemically or electrostatically with metal ions in the metal organic framework and functional groups on the graphene surface to form a stable complex, thereby avoiding the degradation of material properties, and the functional groups in the fulvic acid can absorb ultraviolet rays and reduce the transmittance of ultraviolet rays by adsorption or chemical bonding, thereby improving the anti-ultraviolet performance of the resin material. BRIEF DESCRIPTION OF THE DRAWINGS

[0030] Figure 1This is a flow chart of a method for preparing a composite material for a one-time, paint-free photovoltaic frame according to an embodiment of the present invention. DETAILED DESCRIPTION

[0031] The following will be combined with the drawings in the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0032] Example 1

[0033] A composite material for a one-time molding photovoltaic frame without painting, comprising the following components: 8 parts of bisphenol A epoxy resin E-55, 10 parts of bisanhydride precuring body, 0.8 parts of anti-ultraviolet nano additives, 1 part of triphenyl phosphate and 0.02 parts of BYK-022 defoaming agent;

[0034] A method for preparing a composite material for a one-time molding photovoltaic frame without painting, such as Figure 1 As shown, the following steps are included:

[0035] S1: Preparation of graphene-loaded nanoorganic metal particles

[0036] S1.1: 4 parts of 2-sulfonated terephthalic acid and 0.6 parts of anhydrous sodium acetate are placed in a container, and then 20 parts of N, N-dimethylformamide are added, and magnetic stirring is performed at a speed of 250 rpm for 30 minutes to obtain a 2-sulfonated terephthalic acid solution, and then 2 parts of Al(NO3)3·9H2O and 25 parts of N, N-dimethylformamide are mixed and magnetic stirring is performed until Al(NO3)3·9H2O is completely dissolved to obtain an Al(NO3)3 solution;

[0037] S1.2: 0.3 parts of flake graphite powder are placed in a container, 4 parts of 35% ethanol solution are added, and then stirred at a stirring speed of 400 rpm for 10 minutes, and filtered and dried after standing for 15 minutes to obtain clean flake graphite, and the clean flake graphite and 0.2 parts of polyvinyl pyrrolidone are mixed evenly and placed in a container, 8 parts of N, N-dimethylformamide are added and stirred evenly, and then placed in an ultrasonic disperser, and ultrasonic treatment is performed at an ultrasonic power of 50w for 3 hours to obtain a graphene dispersion;

[0038] S1.3: The 2-sulfonate terephthalic acid solution and Al(NO3)3 solution obtained in step S1.1 are mixed and placed in a container, and ultrasonically treated at an ultrasonic frequency of 25 kHz for 15 minutes. The mixture is then transferred to a reactor and heated at 120°C for 10 hours. The mixture is then transferred to an ultrasonic disperser, and the graphene dispersion obtained in step S1.2 is added thereto. The mixture is ultrasonically treated at an ultrasonic frequency of 25 kHz for 8 minutes. The mixture is then transferred to a reactor and heated at 120°C for 60 hours to obtain a mixed reaction liquid. After the reactor is naturally cooled to room temperature, the mixed reaction liquid is placed in a centrifuge and centrifuged at 8000 rpm for 5 minutes. The mixture is then filtered and washed twice with N,N-dimethylformamide and methanol, respectively, to obtain graphene-loaded nano-organic metal particles.

[0039] S2: Preparation of UV-resistant nano-additives

[0040] S2.1: dissolving fulvic acid in a sodium hydroxide solution having a concentration of 0.1 g / L to prepare a fulvic acid alkali solution having a concentration of 0.06 g / L, then adding 0.1 wt% of hexadecyltrimethylammonium bromide, stirring evenly, adding HCl solution to adjust the pH to 7.2, and then filtering with a 0.5 μm filter membrane to obtain a fulvic acid solution;

[0041] S2.2: Place the graphene-loaded nano-organic metal particles obtained in step S1.3 in 120 parts of fulvic acid solution, add 0.02wt% of glutaraldehyde, and then continue stirring at 200rpm for 8 hours, and then centrifuge at 6000rpm for 4 minutes to obtain fulvic acid-doped nanoparticles, wash them twice with methanol and deionized water respectively, and then place them in a vacuum drying oven at 60°C for 20 hours to obtain anti-UV nano-additives.

[0042] S3: Preparation of dianhydride precured body and epoxy resin compound

[0043] S3.1: α-terpinene and maleic anhydride are placed in a container at a molar ratio of 1:1, 0.1wt% benzenesulfonic acid is added, and then 40 times the mass of dichloromethane is added, and the mixture is stirred evenly and heated to 60°C. The mixture is kept warm for 10 hours, and the reaction solution is stirred for 10 minutes every 40 minutes during the reaction. After stopping the heating, the mixture is naturally cooled to room temperature, and then filtered to remove solid impurities. The mixture is then placed in a rotary evaporator and rotary evaporated at 80 rpm at 40°C until the mass does not change, thereby obtaining terpene maleic anhydride;

[0044] S3.2: Grind 1 part of tetrafluorophthalic anhydride into powder, pass through a 180-mesh sieve, and place it in an ultrasonic water bath with 4 parts of terpene maleic anhydride to mix evenly. The temperature of the ultrasonic water bath is 60°C and the ultrasonic frequency is 28kHz to obtain a dianhydride suspension. Maintain the temperature at 40°C, drain 1 part of bisphenol A epoxy resin E-55 along a glass rod into the dianhydride suspension, and stir for 10 minutes to obtain a dianhydride precured body.

[0045] S3.3: Place 8 parts of bisphenol A epoxy resin E-55, 10 parts of dianhydride precured body, 0.8 parts of anti-UV nano additives, 1 part of triphenyl phosphate and 0.02 parts of BYK-022 defoaming agent in a container, stir at 40°C and 500 rpm for 20 minutes to obtain a composite material for one-time molding of photovoltaic frames without painting.

[0046] Example 2

[0047] A composite material for a one-time molding photovoltaic frame without painting, comprising the following components: 10 parts of bisphenol A epoxy resin E-55, 12 parts of bisanhydride precuring body, 1 part of anti-ultraviolet nano additive, 1.5 parts of triphenyl phosphate and 0.03 parts of BYK-022 defoaming agent;

[0048] A method for preparing a composite material for a one-time molding photovoltaic frame without painting, such as Figure 1 As shown, the following steps are included:

[0049] S1: Preparation of graphene-loaded nanoorganic metal particles

[0050] S1.1: 6 parts of 2-sulfonated terephthalic acid and 0.8 parts of anhydrous sodium acetate are placed in a container, and then 25 parts of N, N-dimethylformamide are added, and magnetic stirring is performed at a speed of 250 rpm for 30 minutes to obtain a 2-sulfonated terephthalic acid solution, and then 3 parts of Al(NO3)3·9H2O and 30 parts of N, N-dimethylformamide are mixed and magnetic stirring is performed until Al(NO3)3·9H2O is completely dissolved to obtain an Al(NO3)3 solution;

[0051] S1.2: 0.5 parts of flake graphite powder are placed in a container, 5 parts of 35% ethanol solution are added, and then stirred at a stirring speed of 400 rpm for 10 minutes, and filtered and dried after standing for 15 minutes to obtain clean flake graphite, and the clean flake graphite and 0.3 parts of polyvinyl pyrrolidone are mixed and placed in a container, 10 parts of N, N-dimethylformamide are added and stirred, and then placed in an ultrasonic disperser, and ultrasonic treatment is performed at an ultrasonic power of 50w for 3 hours to obtain a graphene dispersion;

[0052] S1.3: The 2-sulfonate terephthalic acid solution and Al(NO3)3 solution obtained in step S1.1 are mixed and placed in a container, and ultrasonically treated at an ultrasonic frequency of 25 kHz for 15 minutes. The mixture is then transferred to a reactor and heated at 120°C for 10 hours. The mixture is then transferred to an ultrasonic disperser, and the graphene dispersion obtained in step S1.2 is added thereto. The mixture is ultrasonically treated at an ultrasonic frequency of 25 kHz for 8 minutes. The mixture is then transferred to a reactor and heated at 120°C for 60 hours to obtain a mixed reaction liquid. After the reactor is naturally cooled to room temperature, the mixed reaction liquid is placed in a centrifuge and centrifuged at 8000 rpm for 5 minutes. The mixture is then filtered and washed twice with N,N-dimethylformamide and methanol, respectively, to obtain graphene-loaded nano-organic metal particles.

[0053] S2: Preparation of UV-resistant nano-additives

[0054] S2.1: dissolving fulvic acid in a sodium hydroxide solution having a concentration of 0.1 g / L to prepare a fulvic acid alkali solution having a concentration of 0.08 g / L, then adding 0.2 wt % of hexadecyltrimethylammonium bromide, stirring evenly, adding HCl solution to adjust the pH to 7.2, and then filtering with a 0.5 μm filter membrane to obtain a fulvic acid solution;

[0055] S2.2: Place the graphene-loaded nano-organic metal particles obtained in step S1.3 in 150 parts of fulvic acid solution, add 0.03wt% of glutaraldehyde, and then continue stirring at 200rpm for 8 hours, and then centrifuge at 6000rpm for 4 minutes to obtain fulvic acid-doped nanoparticles, wash them twice with methanol and deionized water respectively, and then place them in a vacuum drying oven at 60°C for 20 hours to obtain anti-UV nano-additives.

[0056] S3: Preparation of dianhydride precured body and epoxy resin compound

[0057] S3.1: α-terpinene and maleic anhydride are placed in a container at a molar ratio of 1:1.05, 0.5wt% benzenesulfonic acid is added, and then 60 times the mass of dichloromethane is added, and the mixture is stirred evenly and heated to 60°C. The mixture is kept warm for 10 hours, and the reaction solution is stirred for 10 minutes every 40 minutes during the reaction. After stopping the heating, the mixture is naturally cooled to room temperature, and then filtered to remove solid impurities. The mixture is then placed in a rotary evaporator and rotary evaporated at 80 rpm at 40°C until the mass does not change, thereby obtaining terpene maleic anhydride;

[0058] S3.2: Grind 2 parts of tetrafluorophthalic anhydride into powder, pass through a 180-mesh sieve, and place together with 6 parts of terpene maleic anhydride in an ultrasonic water bath and mix evenly. The temperature of the ultrasonic water bath is 60°C and the ultrasonic frequency is 28kHz to obtain a dianhydride suspension. Maintain the temperature at 40°C, drain 2 parts of bisphenol A epoxy resin E-55 along a glass rod into the dianhydride suspension, and stir for 10 minutes to obtain a dianhydride precured body.

[0059] S3.3: Place 10 parts of bisphenol A epoxy resin E-55, 12 parts of dianhydride precured body, 1 part of anti-UV nano additive, 1.5 parts of triphenyl phosphate and 0.03 parts of BYK-022 defoaming agent in a container, stir at 40°C and 500 rpm for 20 minutes to obtain a composite material for one-time molding of photovoltaic frames without painting.

[0060] Example 3

[0061] A composite material for a one-time molding photovoltaic frame without painting, comprising the following components: 8 parts of bisphenol A epoxy resin E-55, 10 parts of bisanhydride precuring body, 0.8 parts of anti-ultraviolet nano additives, 1 part of triphenyl phosphate and 0.02 parts of BYK-022 defoaming agent;

[0062] A method for preparing a composite material for a one-time molding photovoltaic frame without painting, such as Figure 1 As shown, the following steps are included:

[0063] S1: Preparation of graphene-loaded nanoorganic metal particles

[0064] S1.1: 4 parts of 2-sulfonated terephthalic acid and 0.6 parts of anhydrous sodium acetate are placed in a container, and then 20 parts of N, N-dimethylformamide are added, and magnetic stirring is performed at a speed of 300 rpm for 35 minutes to obtain a 2-sulfonated terephthalic acid solution, and then 2 parts of Al(NO3)3·9H2O and 25 parts of N, N-dimethylformamide are mixed and magnetic stirring is performed until Al(NO3)3·9H2O is completely dissolved to obtain an Al(NO3)3 solution;

[0065] S1.2: 0.3 parts of flake graphite powder are placed in a container, 4 parts of 40% ethanol solution are added, and then stirred at a stirring speed of 500 rpm for 15 minutes, and filtered and dried after standing for 20 minutes to obtain clean flake graphite, and the clean flake graphite and 0.2 parts of polyvinyl pyrrolidone are mixed evenly and placed in a container, 8 parts of N, N-dimethylformamide are added and stirred evenly, and then placed in an ultrasonic disperser, and ultrasonic treatment is performed at an ultrasonic power of 60w for 5 hours to obtain a graphene dispersion;

[0066] S1.3: The 2-sulfonate terephthalic acid solution and Al(NO3)3 solution obtained in step S1.1 are mixed and placed in a container, and ultrasonically treated at an ultrasonic frequency of 30 kHz for 20 minutes, and then transferred to a reactor and heated at a temperature of 140°C. After 12 hours, the mixture is transferred to an ultrasonic disperser, and the graphene dispersion obtained in step S1.2 is added, and ultrasonically treated at an ultrasonic frequency of 30 kHz for 10 minutes. The mixture is then transferred to a reactor and heated at 140°C for 65 hours to obtain a mixed reaction liquid. After the reactor is naturally cooled to room temperature, the mixed reaction liquid is placed in a centrifuge and centrifuged at a speed of 10,000 rpm for 8 minutes, and then filtered. The mixture is washed three times with N,N-dimethylformamide and methanol, respectively, to obtain nano-organic metal particles loaded with graphene.

[0067] S2: Preparation of UV-resistant nano-additives

[0068] S2.1: dissolving fulvic acid in a sodium hydroxide solution having a concentration of 0.2 g / L to prepare a fulvic acid alkali solution having a concentration of 0.06 g / L, then adding 0.1 wt% of hexadecyltrimethylammonium bromide, stirring evenly, adding HCl solution to adjust the pH to 7.5, and then filtering with a 0.6 μm filter membrane to obtain a fulvic acid solution;

[0069] S2.2: Place the graphene-loaded nano-organic metal particles obtained in step S1.3 in 120 parts of fulvic acid solution, add 0.02wt% glutaraldehyde, and then continue stirring at 250rpm for 12 hours, and then centrifuge at 7000rpm for 5 minutes to obtain fulvic acid-doped nanoparticles, wash them with methanol and deionized water three times respectively, and then place them in a vacuum drying oven at 65°C for 24 hours to obtain anti-UV nano-additives.

[0070] S3: Preparation of dianhydride precured body and epoxy resin compound

[0071] S3.1: α-terpinene and maleic anhydride are placed in a container at a molar ratio of 1:1, 0.1wt% benzenesulfonic acid is added, and then 60 times the mass of dichloromethane is added, and the mixture is stirred evenly and heated to 80°C. The mixture is kept warm for reaction for 12 hours, and the reaction solution is stirred for 15 minutes every 60 minutes during the reaction. After stopping the heating, the mixture is naturally cooled to room temperature, and then filtered to remove solid impurities. The mixture is then placed in a rotary evaporator and rotary evaporated at 50°C at a speed of 100 rpm until the mass does not change, thereby obtaining terpene maleic anhydride;

[0072] S3.2: Grind 1 part of tetrafluorophthalic anhydride into powder, pass through a 200-mesh sieve, and mix well with 4 parts of terpene maleic anhydride in an ultrasonic water bath, the temperature of the ultrasonic water bath is 65°C, the ultrasonic frequency is 30kHz, and a dianhydride suspension is obtained. The temperature is maintained at 50°C, and 1 part of bisphenol A epoxy resin E-55 is drained into the dianhydride suspension along a glass rod, and stirred for 15 minutes to obtain a dianhydride precured body;

[0073] S3.3: Place 8 parts of bisphenol A epoxy resin E-55, 10 parts of dianhydride precured body, 0.8 parts of anti-UV nano additives, 1 part of triphenyl phosphate and 0.02 parts of BYK-022 defoaming agent in a container, stir at 50°C and 600 rpm for 30 minutes to obtain a composite material for one-time molding of photovoltaic frames without painting.

[0074] Comparative Example 1

[0075] Compared with Example 1, the difference of Comparative Example 1 is that, in Comparative Example 1, tetrafluorophthalic anhydride is not added in step S3.2, and 1 part of bisphenol A epoxy resin E-55 is directly drained along a glass rod into 5-terpene maleic anhydride at 40°C to obtain a terpene maleic anhydride precured body, and the remaining steps are the same as those in Example 1. The obtained composite material for coating-free one-time molding of photovoltaic frames is recorded as Comparative Example 1.

[0076] Comparative Example 2

[0077] Compared with Example 1, the difference of Comparative Example 2 is that step S3.1 is removed in Comparative Example 2, and the terpene maleic anhydride in step S3.2 is replaced with an equal mass of methyl nadic anhydride to obtain a dianhydride precured body, and the remaining steps are the same as those in Example 1. The obtained composite material for coating-free one-time molding of photovoltaic frames is recorded as Comparative Example 2.

[0078] Comparative Example 3

[0079] Compared with Example 1, the difference of Comparative Example 3 is that Comparative Example 3 removes step S1, replaces the nano-organic metal particles loaded with graphene in step S2.2 with graphene of equal mass to obtain an anti-ultraviolet nano-additive, and the remaining steps are the same as Example 1. The obtained composite material for painting-free one-time molding of photovoltaic frames is recorded as Comparative Example 3.

[0080] Comparative Example 4

[0081] Compared with Example 1, the difference of Comparative Example 4 is that Comparative Example 4 removes step S2, replaces the anti-UV nano-additive in step S3.3 with an equal mass of graphene-loaded nano-organic metal particles, and the remaining steps are the same as Example 1. The prepared composite material for painting-free one-time molding of photovoltaic frames is recorded as Comparative Example 4.

[0082] Experiment 1: Take the composite materials for coating-free one-time molding photovoltaic frames prepared in Examples 1-3 and Comparative Examples 1-4, add them into a twin-screw extruder, extrude them at 200°C and 250rpm, and then make resin strips with a thickness of 5mm and a length and width of 5cm×2cm by drawing, cooling and cutting. Test the tensile strength according to ISO527 standard, recorded as Rm0; test the 23°C cantilever beam notched impact strength and 60°C cantilever beam notched impact strength according to ISO180 standard, and the data are recorded as 23°C impact strength and 60°C impact strength. Impact strength; heat deformation temperature was tested according to ISO75 standard, and the test condition was 0.45MPa; ultraviolet irradiation was carried out according to IEC62790 standard, and the lighting condition was 120kWH for 2000 hours, and then the tensile strength after illumination was tested according to ISO527 standard, recorded as Rm1, and the tensile strength decrease rate after illumination was calculated as (Rm0-Rm1) / Rm0×100%. The lower the tensile strength decrease rate after illumination, the better the anti-ultraviolet performance. Each test experiment was carried out three times and the average value was taken. The test results were recorded and tabulated, as shown in Table 1.

[0083] Table 1: Properties of resin specimens

[0084]

[0085] It can be seen from Table 1 that the resin strips prepared from the composite materials for the coating-free one-time molding photovoltaic frame of Examples 1-3 are better than those of Comparative Examples 1-4 in terms of the comprehensive strength of the materials reflected in the tensile strength test and the Izod notched impact strength test at 23°C and 60°C, the thermal stability of the materials reflected in the heat deformation temperature test, and the anti-ultraviolet performance of the materials reflected by the tensile strength decrease rate after illumination. It can be seen from Example 1, Comparative Example 1 and Comparative Example 2 that tetrafluorophthalic anhydride can improve the strength and thermal stability of the resin, and that the strength and thermal stability are reduced by replacing terpene maleic anhydride with methyl nadic anhydride, a curing agent of the same type, which can prove that tetrafluorophthalic anhydride and terpene maleic anhydride have a synergistic effect, which can effectively improve the thermal stability of epoxy resin, reduce its thermal expansion coefficient, and enhance its strength;

[0086] And it can be seen from Example 1 and Comparative Example 3 that without preparing nano-organic metal particles to load graphene, the prepared resin material not only has reduced UV resistance and strength, but also has a slightly reduced thermal stability, which can prove that the Al-based metal organic framework can also provide Al ultraviolet shielding and improve compatibility with epoxy resin, thereby improving strength and thermal stability.

[0087] It can be seen from Example 1 and Comparative Example 4 that the treatment of the graphene-loaded nano-organic metal particles without preparing a fulvic acid solution will lead to a decrease in the UV resistance of the resin material. It can be proved that fulvic acid can absorb ultraviolet rays, thereby improving the UV resistance of the resin material, and the strength and thermal stability are also slightly reduced. It is speculated that fulvic acid contains a large number of phenolic hydroxyl groups, carboxyl groups and other functional groups, which can improve the compatibility with various components, thereby enhancing the strength and thermal stability.

[0088] The above embodiments are merely illustrative of the principles and effects of the present invention, and are not intended to limit the present invention. Anyone familiar with the art may modify or alter the above embodiments without departing from the spirit and scope of the present invention. Therefore, all equivalent modifications or alterations made by a person of ordinary skill in the art without departing from the spirit and technical ideas disclosed by the present invention shall still be covered by the claims of the present invention.

Claims

1. A composite material for a one-time forming photovoltaic frame without painting, characterized in that: Includes the following components: 8-10 parts of bisphenol A epoxy resin E-55, 10-12 parts of dianhydride precured body, 0.8-1 parts of anti-ultraviolet nano additives, 1-1.5 parts of triphenyl phosphate and 0.02-0.03 parts of BYK-022 defoamer; The dianhydride precured body is prepared by heating alpha-terpinene, maleic anhydride and catalyst benzenesulfonic acid in a dichloromethane solvent to obtain terpene maleic anhydride, ultrasonically mixing with ground tetrafluorophthalic anhydride, and then adding bisphenol A epoxy resin E-55 and stirring evenly. The anti-ultraviolet nano additive is firstly prepared by reacting 2-sulfonate terephthalic acid, Al(NO3)3·9H2O and flake graphite powder with N,N-dimethylformamide to prepare 2-sulfonate terephthalic acid solution, Al(NO3)3 solution and graphene dispersion respectively, then mixing them for high-temperature heating reaction, centrifugally filtering to obtain nano-organic metal particles loaded with graphene, and then dissolving fulvic acid in sodium hydroxide solution, adding a surfactant to obtain a fulvic acid solution, and then mixing the nano-organic metal particles loaded with graphene, glutaraldehyde and the fulvic acid solution to stir the reaction, and then washing and drying to obtain the anti-ultraviolet nano additive.

2. A method for preparing a composite material for a one-time, paint-free photovoltaic frame, characterized in that: The preparation method is used to prepare the composite material for one-time molding of photovoltaic frames without painting as provided in claim 1. The following steps are involved: S1: Preparation of graphene-loaded nano-organic metal particles; S2: Preparation of UV-resistant nano-additives; S3: Preparation of dianhydride precured body and compounding of epoxy resin.

3. The method for preparing a composite material for a one-time molding photovoltaic frame without painting according to claim 2, characterized in that: Step S1 prepares graphene-loaded nano-organic metal particles, comprising the following steps: S1.1: 4-6 parts of 2-sulfonated terephthalic acid and 0.6-0.8 parts of anhydrous sodium acetate are placed in a container, and then 20-25 parts of N, N-dimethylformamide are added, and magnetic stirring is performed at a speed of 250-300 rpm for 30-35 minutes to obtain a 2-sulfonated terephthalic acid solution, and then 2-3 parts of Al(NO3)3·9H2O and 25-30 parts of N, N-dimethylformamide are mixed and magnetic stirring is performed until Al(NO3)3·9H2O is completely dissolved to obtain an Al(NO3)3 solution; S1.2: 0.3-0.5 parts of flake graphite powder are placed in a container, 4-5 parts of ethanol solution with a concentration of 35-40% are added, and then stirred at a stirring speed of 400-500rpm for 10-15 minutes, and filtered and dried after standing for 15-20 minutes to obtain clean flake graphite, and the clean flake graphite and 0.2-0.3 parts of polyvinyl pyrrolidone are mixed and placed in a container, 8-10 parts of N, N-dimethylformamide are added and stirred evenly, and then placed in an ultrasonic disperser, and ultrasonic treatment is performed for 3-5 hours at an ultrasonic power of 50-60w to obtain a graphene dispersion; S1.3: The 2-sulfonate terephthalic acid solution and Al(NO3)3 solution obtained in step S1.1 are mixed and placed in a container, and ultrasonically treated at an ultrasonic frequency of 25-30 kHz for 15-20 minutes, and then transferred to a reactor and heated at 120-140°C for 10-12 hours, and then transferred to an ultrasonic disperser, and the graphene dispersion obtained in step S1.2 is added, and ultrasonically treated at an ultrasonic frequency of 25-30 kHz for 8-10 minutes, and then transferred to a reactor and heated at 120-140°C for 60-65 hours to obtain a mixed reaction liquid. After the reactor is naturally cooled to room temperature, the mixed reaction liquid is placed in a centrifuge and centrifuged at a speed of 8000-10000 rpm for 5-8 minutes, and then filtered, and washed with N,N-dimethylformamide and methanol for 2-3 times respectively to obtain nano-organic metal particles loaded with graphene.

4. The method for preparing a composite material for a one-time molding photovoltaic frame without painting according to claim 3, characterized in that: Step S2: Preparation of anti-ultraviolet nano additives, comprising the following steps: S2.1: dissolving fulvic acid in a sodium hydroxide solution having a concentration of 0.1-0.2 g / L to prepare a fulvic acid alkali solution having a concentration of 0.06-0.08 g / L, then adding 0.1-0.2 wt % of a surfactant, stirring evenly, adding HCl solution to adjust the pH to 7.2-7.5, and filtering using a 0.5-0.6 μm filter membrane to obtain a fulvic acid solution; S2.2: Place the graphene-loaded nano-organic metal particles obtained in step S1.3 in 120-150 parts of fulvic acid solution, add 0.02-0.03wt% glutaraldehyde, and then continue stirring at a speed of 200-250rpm for 8-12 hours, and then centrifuge at a speed of 6000-7000rpm for 4-5 minutes to obtain fulvic acid-doped nanoparticles, wash them with methanol and deionized water 2-3 times respectively, and then place them in a vacuum drying oven at a temperature of 60-65°C for 20-24 hours to obtain an anti-ultraviolet nano-additive.

5. The method for preparing a composite material for a one-time, paint-free photovoltaic frame according to claim 4, characterized in that: Step S3: Preparation of dianhydride precured body and compounding of epoxy resin, The following steps are involved: S3.1: α-terpinene and maleic anhydride are placed in a container at a molar ratio of 1:(1-1.05), 0.1-0.5wt% of benzenesulfonic acid is added, and then 40-60 times the mass of dichloromethane is added, and the mixture is stirred evenly and heated to 60-80°C. The mixture is kept warm for reaction for 10-12 hours, and the reaction solution is stirred for 10-15 minutes every 40-60 minutes during the reaction. After stopping the heating, the mixture is naturally cooled to room temperature, and then filtered to remove solid impurities. The mixture is then placed in a rotary evaporator and rotary evaporated at 40-50°C at a speed of 80-100rpm until the mass does not change, thereby obtaining terpene maleic anhydride; S3.2: Grind 1-2 parts of tetrafluorophthalic anhydride into powder, pass through a 180-200 mesh sieve, and mix them together with 4-6 parts of terpene maleic anhydride in an ultrasonic water bath to obtain a dianhydride suspension, maintain the temperature at 40-50°C, drain 1-2 parts of bisphenol A epoxy resin E-55 into the dianhydride suspension along a glass rod, and stir for 10-15 minutes to obtain a dianhydride precured body; S3.3: 8-10 parts of bisphenol A epoxy resin E-55, 10-12 parts of dianhydride pre-cured body, 0.8-1 parts of anti-ultraviolet nano additives, 1-1.5 parts of triphenyl phosphate and 0.02-0.03 parts of BYK-022 defoamer are placed in a container, and stirred at 40-50° C. at a speed of 500-600 rpm for 20-30 minutes to obtain a composite material for coating-free one-time molding of photovoltaic frames.

6. The method for preparing a composite material for a one-time, paint-free photovoltaic frame according to claim 4, characterized in that: The surfactant in step S2.1 is hexadecyltrimethylammonium bromide.

7. The method for preparing a composite material for a one-time, paint-free photovoltaic frame according to claim 5, characterized in that: Step S3.2: Mix evenly in an ultrasonic water bath, wherein the temperature of the ultrasonic water bath is 60-65°C and the ultrasonic frequency is 28-30kHz.

8. Application of composite materials for one-time molding of photovoltaic frames without painting, characterized in that: The composite material for the one-time molding of a photovoltaic frame without painting as claimed in claim 1 is placed in a double-screw extruder for extrusion, and then pultruded once in a mold to obtain a photovoltaic frame.

Citation Information

Patent Citations

  • Short-fiber-reinforced pultrusion composite material solar energy assembly frame and preparation method thereof

    CN104761880A

  • Modified fiberglass photovoltaic support and processing technology thereof

    CN108912608A

  • An anti-skid wear-resistant layer for a paved solar photovoltaic power generation pavement module

    CN108951350A

  • High-toughness and weather-resistant fiber reinforced plastic photovoltaic scaffold

    CN109111693A

  • Preparation method of composite material solar photovoltaic module frame

    CN111269553A